1995
DOI: 10.1093/nar/23.12.2097
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of cDNA encoding mouse Cdc21 and CDC46 homologs and characterization of the products: physical interaction between P1 (MCM3) and CDC46 proteins

Abstract: Two new mouse genes encoding proteins that belong to the yeast minichromosome maintenance (MCM) protein family, which is involved in the initiation of DNA replication, were isolated and their nucleotide sequence was deternined. They were a putative CDC46WMCM5 homolog and a putative cdc2l homolog. About 30%/o amino acid identity was obtained between members in the family, and >400% t ten the putative mouse and yeast homologs. The expression of these genes was cell-cycle specific at the late G1 to S phase. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
59
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 26 publications
(37 reference statements)
9
59
1
Order By: Relevance
“…The formation of MCM protein complexes has been found in mammals Kimura et al 1995;Musahl et al 1995;Schulte et al 1996;Ishimi et al 1996), Xenopus (Chong et al 1995;Kubota et al 1995;Madine et al 1995a,b;Someya & Shioda 1995;Miyake et al 1996), Drosophila (Su et al 1996) and fission yeast (Okishio et al 1996) in agreement with genetic studies in yeasts (Moir et al 1982;Hennessy et al 1991;Yan et al 1991;Forsburg & Nurse 1994;Takahashi et al 1994). MCM3 appears to be tightly associated with CDC46 in mouse and human cells Kimura et al 1995) and human Cdc21 is shown to interact with other MCM proteins including MCM2 and p85Mcm/hCDC47 Schulte et al 1996).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The formation of MCM protein complexes has been found in mammals Kimura et al 1995;Musahl et al 1995;Schulte et al 1996;Ishimi et al 1996), Xenopus (Chong et al 1995;Kubota et al 1995;Madine et al 1995a,b;Someya & Shioda 1995;Miyake et al 1996), Drosophila (Su et al 1996) and fission yeast (Okishio et al 1996) in agreement with genetic studies in yeasts (Moir et al 1982;Hennessy et al 1991;Yan et al 1991;Forsburg & Nurse 1994;Takahashi et al 1994). MCM3 appears to be tightly associated with CDC46 in mouse and human cells Kimura et al 1995) and human Cdc21 is shown to interact with other MCM proteins including MCM2 and p85Mcm/hCDC47 Schulte et al 1996).…”
Section: Introductionmentioning
confidence: 63%
“…MCM3 appears to be tightly associated with CDC46 in mouse and human cells Kimura et al 1995) and human Cdc21 is shown to interact with other MCM proteins including MCM2 and p85Mcm/hCDC47 Schulte et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular function of MCM proteins has not so far been demonstrated. Using immunoprecipitation, several groups have recently shown that some of the MCM family members interact physically, although there might be some discrepancy between organisms (Madine et al 1995;Musahl et al 1995;Kimura et al 1995;Lei et al 1996;Romanowski et al 1996;Su et al 1996). To understand the biochemical function of MCM proteins, we set out to purify MCM proteins from a fission yeast as an initial step.…”
Section: Introductionmentioning
confidence: 99%
“…The inactivation of human MCM2 protein with antibody consistently inhibits the initiation of DNA replication (6). Interaction between the MCM proteins has been reported in yeast (4,7), and the protein complexes containing MCM proteins are detected in Drosophila (8), Xenopus (9), mouse (10,11), and human cells (12)(13)(14). In human cells, MCM4, -6, and -7 proteins form a stable complex, and MCM2 is loosely associated with this complex (12,15,16).…”
mentioning
confidence: 99%
“…In human cells, MCM4, -6, and -7 proteins form a stable complex, and MCM2 is loosely associated with this complex (12,15,16). MCM3 and -5 proteins also form a stable complex (10,13). All six of the MCM proteins contain DNA-dependent ATPase motifs in a central domain that is conserved from yeast to mammals, and these motifs are found in several enzymes that unwind the DNA duplex (17).…”
mentioning
confidence: 99%